Nanomaterials for Ion Battery Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book describes recent studies in the development of nanomaterials for various secondary batteries, including Li-ion batteries (LIBs), Li–air batteries, and multivalent aqueous batteries. A simple, low-cost, and scalable synthetic process for the development of nanomaterials is another research topic in this book. The recent studies dedicated by researchers in this book highlight the importance of innovative nanostructures and new functional materials, which can open new opportunities for battery research.